2011
DOI: 10.1002/bdra.20791
|View full text |Cite
|
Sign up to set email alerts
|

Variation in FGF1, FOXE1, and TIMP2genes is associated with nonsyndromic cleft lip with or without cleft palate

Abstract: Our results provide for the first time evidence implicating FGF1 in the occurrence of CL/P, and support TIMP2 and WNT9B as novel loci predisposing to CL/P. We have also replicated recently reported significant associations between variants in or near FOXE1 and CL/P. It is likely that variation in FOXE1, TIMP2, and the FGF and Wnt signaling pathway genes confers susceptibility to nonsyndromic CL/P in Northeastern European populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
42
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 37 publications
6
42
0
6
Order By: Relevance
“…A promoter variant in the TIMP2 (rs8179096) gene was also associated with NSCL/P (Letra et al, 2012a), corroborating previous association findings in Europeans (Nikopensius et al, 2011).…”
supporting
confidence: 88%
“…A promoter variant in the TIMP2 (rs8179096) gene was also associated with NSCL/P (Letra et al, 2012a), corroborating previous association findings in Europeans (Nikopensius et al, 2011).…”
supporting
confidence: 88%
“…Multiple other genome-wide linkage scans were performed for CL/P, each of which noted a number of positive signals; however, owing to limited sample size, few individual study results reached the standard levels of genome-wide significance [LOD scores ≥ 3.2 (73) for the typical 400-microsatellite-marker panel] until a consortium of research groups pooled their studies and achieved the first genome-wide significant results for CL/P in regions 1q32, 2p, 3q27-28, 9q21, 14q21-24, and 16q24 (86, 87). Follow-up fine mapping of these regions showed significant results for single-nucleotide polymorphisms (SNPs) in IRF6 , which had been previously associated in candidate gene studies (114) and was later also identified by genome-wide association studies (9, 13, 79), and in FOXE1 , which was later confirmed and strengthened with the results in other populations and from expression studies (78, 96, 107, 140). …”
Section: Evolution Of Human Genetic Studies Of Orofacial Cleftsmentioning
confidence: 55%
“…A search for potential (vertebrate) transcription factors binding to CpGs 83–85 revealed that CpG85 was a preferred target for HNF (or Forkhead box) proteins (Table 4), whereas CpG83 is a potential target for ISGF3, ELF-1, SP1 and NF-AT proteins. Foxc2 and Foxe1 have been identified as candidate genes for human syndromic and nonsyndromic palatal clefting, highlighting the importance of HNF proteins to palate development and the potentially critical role of CpG85 [64,65]. We therefore demonstrate, for the first time, that the developmental expression of Sox4 in the secondary palate is regulated via temporal changes in DNA methylation occurring at critical CpG residues located distal to the putative promoter.…”
Section: Discussionmentioning
confidence: 77%